Physiological Biomimetic Culture System for Pig and Human Heart Slices. Issue 6 (30th August 2019) - Ou, Qinghui; Jacobson, Zoë; Abouleisa, Riham R.E.; Tang, Xian-Liang; Hindi, Sajedah M.; Kumar, Ashok; Ivey, Kathryn N.; Giridharan, Guruprasad; El-Baz, Ayman; Brittian, Kenneth; Rood, Benjamin; Lin, Ying-Hsi; et al.
Abstract : Rationale: Preclinical testing of cardiotoxicity and efficacy of novel heart failure therapies faces a major limitation: the lack of an in situ culture system that emulates the complexity of human heart tissue and maintains viability and functionality for a prolonged time. Objective: To develop a reliable, easily reproducible, medium-throughput method to culture pig and human heart slices under physiological conditions for a prolonged period of time. Methods and Results: Here, we describe a novel, medium-throughput biomimetic culture system that maintains viability and functionality of human and pig heart slices (300 µm thickness) for 6 days in culture. We optimized the medium and culture conditions with continuous electrical stimulation at 1.2 Hz and oxygenation of the medium. Functional viability of these slices over 6 days was confirmed by assessing their calcium homeostasis, twitch force generation, and response to β-adrenergic stimulation. Temporal transcriptome analysis using RNAseq at day 2, 6, and 10 in culture confirmed overall maintenance of normal gene expression for up to 6 days, while over 500 transcripts were differentially regulated after 10 days. Electron microscopy demonstrated intact mitochondria and Z-disc ultra-structures after 6 days in culture under our optimized conditions. This biomimetic culture system was successful in keeping human heart slices completely viable and functionally and structurally intact for 6 days in culture. We also used this system to demonstrate the effects of a novel gene therapy approach in human heart slices. Furthermore, this culture system enabled the assessment of contraction and relaxation kinetics on isolated single myofibrils from heart slices after culture. Conclusions: We have developed and optimized a reliable medium-throughput culture system for pig and human heart slices as a platform for testing the efficacy of novel heart failure therapeutics and reliable testing of cardiotoxicity in a 3-dimensional heart model. Visual Overview: An online visual overview is available for this article. Abstract : Supplemental Digital Content is available in the text.